Conflicts Strategies Involving the Pupils, Parents, and Teachers - Bilbar Jr., Geronimo (IJRDO- Journal of Educational Research, 2020)
This research used the descriptive method to determine the conflict strategies involving the pupils, parents, and teachers in in Manduaw Elementary School, Bayawan City Division, Negros Oriental, Philippines. The quantitative data were gathered from the random sample of the pupils and their parents and complete enumeration of teachers . Also, the researcher utilized a self-made and modified questionnaire to assess the effective conflict strategies involving pupils, parents and teachers. Descriptive method was used in this study. The statistical tools used in the analysis of the data were percentage, mean, and weighted mean. The study found out that the extent of conflict strategies in terms of competing, collaborating, avoiding, and compromising was sometimes on pupils and parents while often and sometimes for teachers.